Коаксиальная тепловая труба для охлаждения отражателя лазера - Gershuni, A. N.; Nishchik, A. P. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
The paper presents the development and research results for a coaxial heat pipe designed for cooling of a reflector of a solid-state laser. A coaxial cylindrical heat pipe, designed to cool the laser reflector, provides that the temperature of the heat-removing surface does not exceed 120°C at any orientation in the gravitational field, if the heat is removed by forced convection of air with the temperature of 60°C in a pulsed mode of heat flow supply of 300 W. Thermal resistance of the developed heat pipe is 0,03 K/W, the specific thermal resistance — 1,1.10–3 m2.K/W. The developed cooling system based on the evaporation-condensation principle, allows ensuring temperature uniformity of the cooling surface at low thermal resistance.